Assessing the contribution of mobile management information systems to work-life balance and job satisfaction among university teachers in China: A focus on system accessibility and efficiency - Hui Zhang; Oscar Dousin (Journal of Information Systems Engineering and Management, 2024)
Mobile management information systems, job satisfaction, and work-life balance affect Chinese university teachers, examined in the study. The quantitative study surveyed 516 university teachers on a 5-point Likert scale. The research included instructors with diverse mobile management information systems backgrounds due to this systematic approach. Work-life balance, system accessibility, and teaching experience increased university professors' job satisfaction and balance, the study found. Regression analyses showed that teaching experience, system accessibility, and technology proficiency significantly affect outcomes. Teaching experience and system accessibility improve university professors' job satisfaction and work-life balance. Mobile management information systems and teaching experience boost teacher job satisfaction and work-life balance. We must integrate advanced technology and make systems user-friendly and accessible to all educators, regardless of technology background. The study found that teachers need ongoing technological training to use these systems effectively, improving job satisfaction and work-life balance. Workinglife balance, mobile management information system accessibility, and comprehensive teacher technological training are recommended by the study. These factors improve work-life balance and job satisfaction by integrating mobile management information systems into education. Policymakers and administrators should consider cultural and contextual factors and provide personalized support to educators. This study shows how mobile management information systems, work-life balance, and job satisfaction can help administrators, educators, and policymakers understand Chinese educators' technology use. Technology in instruction, culture and personality affect Chinese university professors' well-being.